Filial cannibalism in rainbow boas (Epicrates cenchria and E. assisi) - Gabriela Ramos; Tiago de Oliveira Lima; Selma Maria de Almeida-Santos (Theriogenology Wild)
Cannibalism, or intraspecific predation, refers to the practice in which an individual completely or partially consumes another conspecific. Filial cannibalism occurs when parents consume their own offspring, whether they are alive or stillborn. This study describes filial cannibalism behavior in just one female of each species, Amazon rainbow boa (Epicrates cenchria) and the Caatinga rainbow boa (E. assisi). We observed that female E. cenchria and E. assisi only consumed atretic eggs. A female E. cenchria consumed two out of the eight atretic eggs she delivered, while sparing the four neonates and the only stillborn fetus in her litter. A female E. assisi consumed two out of the four atretic eggs and attempted to ingest the amniotic sacs and liquid yolk throughout the entire observation, sparing two neonates. This is the first documented record of such behavior in E. assisi.